The joint response of stock and foreign exchange markets to macroeconomic surprises: Using US and Japanese data - Mun, Kyung-Chun (Journal of Banking & Finance, 2012)
This paper investigates the joint response of stock and foreign exchange (FX) market returns to macroeconomic surprises, employing a system method of estimation that allows for the cross-country and cross-market interaction for asset returns and risk premia. Using US and Japanese data, we find that US stock markets are asymmetrically responsive to domestic developments in output growth and interest rates but are not influenced by macroeconomic surprises from Japan. The surprise in the FX market seems to affect stock markets in the US and Japan, respectively. In particular, we find that the interest rate surprise in the US and inflation surprise in Japan tend to overstate the impact that these surprises would have on the respective stock market. The impact of the surprises would appear smaller if macroeconomic developments induced by the FX market were incorporated into the model.